A comparison study of foley catherer ballon volume 40cc versus 80cc for mechanical induction of labour : a prospective randomised control trial - Maria Muhammad (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
The aim of this study is to observe the change in the Bishop Score following mechanical induction of labour in women by using Foley catheter balloon inflated with different volumes: 80cc (test group) versus 40cc (control group). This study also aims to compare the number of successful vaginal births from the two groups. This is a prospective randomised control study, conducted in Hospital Raja Perempuan Zainab II in Kota Bharu, Kelantan Darul Naim. A total of 150 consented women, each with a singleton, viable pregnancy at term, participated in the study. 74 women were randomised and each was induced with a Foley catheter balloon with a volume of 80cc, while the other 76 women were each induced with a Foley catheter balloon with a volume of 40cc. The primary outcome compares the change in the Bishop Score and the rate of successful vaginal delivery. Secondary outcomes include the time consumed from induction to delivery, maternal and neonatal complications, and patient's acceptance. As for the change in the Bishop Score, there is a significant difference in the mean of Bishop Score change between the test and control groups (p=0.005). Successful vaginal delivery among women induced with the 80cc volume was 83% compared to 51% among those induced with the 40cc volume, which is statistically significant (p<0.001). The mean time consumed from induction to delivery vary significantly between the two groups, with 33.5 ±16 hours in the test group, and 44.2 ± 23 hours in the control group (p=0.01). All women in this study showed no sign of post-delivery infection, whereas incidence of postpartum haemorrhage is not significant in both groups, although the test group had more numbers by comparison. Almost all babies were born with good Apgar Scores (Apgar Score of 7 and more, at 5 minutes of life) and none of them had any sign of post-delivery infection. There is also no significant difference of neonatal admission in both groups. Almost all women in this study rated one or two on the Visual Analogue Score (VAS) for pain rating, indicating mild discomfort during the Foley catheter's insertion. In conclusion, the induction of labour using a Foley catheter balloon with a volume of 80cc was well tolerated by patients, resulted in significant cervical score changes and higher vaginal delivery rates without increasing maternal or foetal morbidities.